CLAY AND PHOSPHORUS LOSSES BY EROSION IN OXISOL WITH SUGARCANE RESIDUES - De Paula, Daniela T. [UNESP]; Martins Filho, Marcilio V. [UNESP]; Farias, Vera L. Da S. [UNESP]; Siqueira, Diego S. [UNESP] (Soc Brasil Engenharia Agricola, 2016)
Considering the importance of nutrients in the soil for the plants development and the soil quality conservation and the quantification relevance of them for proper soil management, the aims of this research were: (i) to quantify the clay loss, adsorbed and soluble P from interrill erosion influenced by the presence of sugarcane residues on the ground surface; (ii) to determine the minimum percentage of residues to be maintained on the soil surface to not enrich the eroded sediment by clay and soluble P (P-sed) and adsorbed (P-ads). The experimental area is located in Guariba - SP, with soil classified as Red Dystrophic Oxisol. The experiment was designed based on results of previous experiments with residue analysis of variance for 40 plots. These experiments were conducted by our research group, which provided field representation and the establishment of a minimum number of degrees of freedom necessary to ensure normal distribution of results and variance homoscedasticity. The experimental design was completely randomized in a factorial design, 5 treatments with straw sugarcane and 3 repetitions, totaling 15 plots. In the treatments, the straw was manually distributed across the surface of the soil in amounts of 0; 0.16; 0.35; 0.52 to 0.7 Kg by plot, giving 0% coverage (SC0), 25% (SC25), 50% (SC50), 75% (SC75) and 100% (SC100), respectively. The experimental plots were subjected to simulated rain with average intensity of 60 mm h(-1) for 65 minutes. To avoid enrichment ratio (ER) of the sediment eroded by Psed, Pads and clay, a minimum soil surface coverage (SC) of 42% is necessary.
Keywords: interrill erosion; simulated rainfall; vegetation cover